2019
DOI: 10.22201/fmvz.24486760e.2018.4.642
|View full text |Cite
|
Sign up to set email alerts
|

Can C-phycocyanin be used as a sperm protector?

Abstract: C-phycocyanin (C-PC) is a biocompound extracted from Arthrospira maxima. It is a chromophore-protein complex, with antioxidant properties. Its ability to prevent oxidative stress allows for diverse medical applications. This study evaluates the use of C-PC as a protein supplement and an antioxidant for in-vitro sperm preservation in a short-term extender. Viability, progressive motility, DNA damage and percentage of reactive oxygen species where assessed in Swine (Sus scrofa domesticus) sperm stored for up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
14

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 22 publications
(31 reference statements)
0
2
0
14
Order By: Relevance
“…Another theory for the beneficial effects of SPE on the vital parameters of the cryopresreved spermatozoa may be attributed in fact to its antioxidant activities, scavenge ROS and protect sperm cell from toxic oxygen metabolites causing lipid peroxidation of sperm plasma membrane during cryopreservation ( Bilodeau et al, 2001 ). Antonio Marcos et al (2018) reported that the addition of C-phycocyanin as an extracted compound from Arthrospira maxima in the boar semen extender could control the production of intracellular ROS production that couldy positively reflect on the increase in the percentage of progressive motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another theory for the beneficial effects of SPE on the vital parameters of the cryopresreved spermatozoa may be attributed in fact to its antioxidant activities, scavenge ROS and protect sperm cell from toxic oxygen metabolites causing lipid peroxidation of sperm plasma membrane during cryopreservation ( Bilodeau et al, 2001 ). Antonio Marcos et al (2018) reported that the addition of C-phycocyanin as an extracted compound from Arthrospira maxima in the boar semen extender could control the production of intracellular ROS production that couldy positively reflect on the increase in the percentage of progressive motility.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, Nah et al (2012) demonstrated that spirulina extracts had both antioxidant activity and anti-inflamatory action, in rabbits ( El-Ratel and Gabr, 2020 ; Fouda and Ismail, 2017 ) concluded that addition of spirulina could improve rabbit semen production and its antioxidant potential. C-phycocyanin (C-PC) is considered an extracted biocompound from Arthrospira maxima with an antioxidant property, its addition to swine semen extender resulted in an increase of progressive motility and decrease of the intracellular ROS production ( Antonio Marcos et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…• El sistema glutatión (glutatión peroxidasa/glutatión reductasa) y la catalasa. Además del sistema mencionado anteriormente, existen otros tipos de antioxidantes no enzimáticos que ayudan a mantener las ERO con troladas, por ejemplo: el ácido ascórbico [26], el tocoferol [21] y la C-Ficocianina [24,50].…”
Section: B Antioxidantesunclassified
“…En el caso de Arthrospira maxima, que es una cianobacteria, su ficobiliproteína más abundante es la C-Ficocianina [24,25,50,54,55] y dentro de la estructura química de este biopigmento, se encuentra la ficocianobilina [25]. Las tres ficobiliproteínas más comunes son: Ficoeritrina con cromóforos de ficoeritrobilina, C-Ficocianina y Aloficocianina con cromóforos de ficocianobilina [53].…”
Section: C-ficocianinaunclassified
See 1 more Smart Citation